Pengembangan Karier Sebagai Motivator Kerja Karyawan - Irvianti, Laksmi S. D. (Bina Nusantara University, 2004)
Regarding the importance of employee’s work motivation and how it affects the productivity and the performance of the employees and the company, it’s necessary to have certain ways to maintain the motivation, in order to have a better performance. One of the ways is providing career development program for the employees.